The Parametric Change in The Null Subject Parameter and Its Repercussion in PB: A Study of Existential Sentences - Juliana Esposito Marins (Working Papers em Linguística, 2014)
Considering the changes that Brazilian Portuguese has been gone through about the Null Subject Parameter remarking, I investigate existential sentences with verbs haver and ter in BP and EP. The research is based on a corpus of popular plays, written between 1840 and 1998. Based on the Theory of Principles and Parameters in the perspective of the Minimalist Program (CHOMSKY 1995), and applying the methodology commonly used in the theory of linguistic variation and change, the objective is to show how the replacement of haver by ter in this type of structure is related to the loss of the possibility of licensing an empty category in the subject position, which is not the case in European Portuguese (EP). The analysis reveals that the possessive verb has started to invade the contexts once occupied by haver, and became the prototypical existential verb.